Horrible Haircut - "Ritchie, Alison" (Egmont Books Ltd USA, 2000)
Mum promises that if she cuts Lucy's hair too short then Lucy can cut her hair in return. Lucy's little brother Johnny decides that Scruff the dog needs a haircut too, and that's when things get really hairy!
Keywords: Children's stories Fiction